THE SIMILARITIES OF FABRIC NAMES IN UZBEK AND ENGLISH LANGUAGES. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article provides a comprehensive study of English fabrics, bilingualism, and the constructivist analysis of information in English. frame. This interpretive study not only provides linguistic insights, but also highlights the cultural, historical, and global dimensions that shape the related lexicon in Uzbek and English. The interplay of tradition and modernity is a linguistic tapestry that reflects the dynamic nature of language evolution in a globalized world. Also, the main focus of the article is on the transfer of the structural structure. semantic analysis of textile terms in Uzbek and English languages.